Marcuse's challenge to education - Kellner, Douglas, 1943- (Rowman & Littlefield Publishers, 2009)
Marcuse's Challenge to Education, a collection of unpublished lecture notes by the thinker himself as well as essays by scholars who have explicated his theories, examines Herbert Marcuse's ground-breaking critique of education as well as his own pedagogical alternatives. Edited by Douglas Kellner, this compilation provides an overview of the various themes of Marcuse's challenges to traditional education and connections with ideas of other radical thinkers ranging from Bloch and Freire to Freud andLacan.